Principales factores de riesgo en mujeres con cáncer de mama atendidas en SOLCA entre los meses enero - junio durante el año 2009 - Coello Carrión, Gabriela L. (2009)
His research paper entitled “Main risk factors in women with breast cancer among SOLCA needs in January - June months for the year 2009”. It aims to demonstrate the importance of risk factors in women with breast cancer, was conducted this prospective, descriptive study in which patients admitted to hospital SOLCA of 325 patients who received mammograms in which 133 patients underwent biopsy which among them 19 patients with breast cancer during January to June 2009. The main risk factors are the age of 50 – 59 years with a rate of 58%, body mass index of 24.9 is higher which corresponds to 84%, age at menarche. The most common is 13 – 15 and more than 16 years to equal 37%, and age of menopause is 45 – 55 years corresponds to 74%. The most common diagnostic method is excisional biopsy which corresponds to 58%. The mortally of all patients treated at the hospital of SOLCA at 0% during the months January to June 2009